OS09.5.A The experience of interval scans for adults living with primary malignant brain tumours. (5th September 2022) - Rudkin, S; Booth, T C; Absolom, K; Latchford, G; Short, S C; Boele, F W
Abstract: Background: People living with primary malignant brain tumours (PMBT) face a complex and unpredictable illness. Throughout the disease course they undergo various treatments and follow-up with regular interval scanning. There are potential costs and benefits to interval scanning, however there is no high-quality evidence to suggest interval scanning is beneficial or whether scans alter outcomes of importance for people living with PMBTs. Yet, interval scanning may exacerbate issues such as uncertainty and anxiety - which impacts on patient quality of life. The aim of this study was to gain an in-depth understanding of how adults living with PMBTs experience and cope with interval scanning. Material and Methods: Twelve patients with a diagnosis of PMBT (glioblastoma n=10; astrocytoma grade 3 n=1; solitary fibrous tumour of the dura grade 3 n=1) under the neuro-oncology teams at Leeds Teaching Hospital NHS Trust and King's College Hospital NHS Foundation Trust took part in the study. They were interviewed remotely about their experiences of interval scans, following a semi-structured interview guide. An abbreviated version of a constructionist grounded theory approach was used to analyse data. Results: Five main themes were generated from the data: 'Living with a PMBT', 'Interval scanning: the difficult times', 'MRI scan: accepting the discomfort', 'Waiting for results: coping with the uncertainty' and 'Results: providing some certainty in uncertainty'. Although most participants found interval scans uncomfortable, they accepted that they were something that they had to do and were using various coping methods to get through the MRI scan. All participants said that the wait between their scan and results was the most difficult part. Despite the difficulties they experienced, all participants said that they would prefer to have interval scans than wait for a change in their symptoms. Most of the time, scans provided relief, gave participants some certainty in an uncertain situation, and a short-term sense of control over their lives. Conclusion: The present study shows that interval scanning is important and highly valued by patients living with PMBT. Although interval scans are anxiety provoking, they appear to help people living with PMBT cope with the uncertainty of their diagnosis.